Phylogenetic Origins of Pseudomonas aeruginosa Isolated from Various Clinical Samples in Iraq - Furqan Mohammed Al-Asady (Medical Journal of Babylon)
Background: Pseudomonas aeruginosa is a significant pathogen associated with severe infections. Objectives: This study aims to investigate the phylogenetic origin of P. aeruginosa isolated in Iraq. Materials and Methods: A total of 150 clinical samples were collected from patients who visited hospitals in nine cities of Iraq between February 2022 and June 2022. Isolates were diagnosed using traditional methods and the polymerase chain reaction technique, and they were assigned designations from PA1 to PA46. Additionally, biofilm formation was assessed using microtiter plates, and the correlation between biofilm grade and antibiotic resistance was investigated. Results: Out of the 150 samples, 46 isolates (31%) of P. aeruginosa were obtained. Results indicated that 34 isolates (74%) were capable of producing biofilm. Fifteen isolates (PA1, PA2, PA3, PA5, PA6, PA7, PA8, PA9, PA11, PA12, PA16, PA19, PA23, PA24, and PA30), obtained from various regions of Iraq, were selected. Whole DNA extraction was performed on these isolates. Subsequently, sequencing of blaTEM, blaCTX-M, and blaSHV genes was conducted, and their genome locations were identified. Phylogenetic tree analysis was performed with the Molecular Evolutionary Genetics Analysis X 10.2.4 software program. The results revealed that one isolate (PA3) originated from the UAE, two isolates (PA6 and PA9) originated from India, three isolates (PA12, PA16, and PA19) originated from Egypt, and another three isolates (PA23, PA24, and PA30) originated from Iran. Conclusions: The study identified the presence of numerous isolates of P. aeruginosa collected from various regions of Iraq, with phylogenetic analysis indicating their origin from other countries.